Narrative change : how changing the story can transform society, business, and ourselves - Hansen, Hans (College teacher) (Columbia University Press, 2020)
"An innovative study of narrative construction in capital defense cases from management professor and death penalty expert. Since 1976, Texas has accounted for more than a third of the nation's 1,400 executions. In cases where the prosecutor seeks the death penalty in Texas, the defendant is sentenced to death 90 percent of the time. In West Texas in 2008, that rate was 98 percent. That's when the newly formed Regional Public Defenders Office for Capital Cases approached management professor Hans Hansen to drastically rethink their strategic approach to death penalty cases. The result? Only one of the eighty criminals charged with the death penalty the team has defended since its inception has been sentenced to death. Hansen conducted a six-year ongoing ethnographic management investigation into how these cases are defended, and how it could be done better. Through narrative construction, a method by which participants produce a narrative to make sense of their organizational context and strategically guide action and decision-making, Hansen and the RPDO identified key flaws in traditional approaches to defending capital cases and set about fixing them. For instance, rather than relying on the DA, they conduct their own separate investigation. And rather than court showdowns, their primary motive is to present mitigating evidence to the prosecutors that will dissuade them from pursuing the death penalty. Under Hansen's guidance, defending attorneys produce strategic narratives for every client, which guide the course of the defense strategies. This book follows the methodology of narrative construction as applied to two key cases: Seth Rose and James Neely. Seth was sentenced to life in prison; James, to death. Using RPDO's success, the cultural shift at Uber, and the author's personal struggles, this book unpacks the methodology of narrative construction and its applications for organizational, social, and institutional change. Hansen shows us how narratives shape our everyday lives, and how we can construct new narratives to enact positive change. Combining ethnography and change management theory, Narrative Management and the Texas Death Penalty provides an unparalleled window into the long-term applications of an innovative model of change"--